Presenting a Structural Model for Predicting Psychological Well-Being Based on Mindfulness with the Mediation of The Meaning in Life and Cognitive Regulation of Emotion in Female Entrance Examination Students - Shakiba Ahmadi; Abbas Javaheri Mohammadi; Hosein Keshavarz Afshar; Seyyed Mohammad Mahdi Reiskarami (پژوهش‌های کاربردی روانشناختی)
The purpose of this study was to present a structural model for predicting psychological well-being in entrance exam students, which was based on mindfulness and mediated by the cognitive regulation of emotion and the meaning of life. It was of the structural equation modeling type in terms of the fundamental intent and the method of collecting correlational data. The statistical population consisted of female students attending secondary institutions in Tehran from 2022 to 2023. These students were selected using the available sampling method, and a total of 271 subjects participated in the research. Psychological well-being scale (PWS), cognitive emotion regulation questionnaire (CERQ), meaning in life questionnaire (MLQ), and five-dimensional mindfulness questionnaire (FFMQ) are included in the research instruments. SPSS24 and AMOS24 software were employed to conduct data analysis using the Pearson correlation and structural equation methods. The results indicated a positive and significant relationship between psychological well-being, mindfulness, the meaning of life, and the cognitive regulation of emotion (P<0.01). Furthermore, the research findings indicated that the mediating role of cognitive regulation of emotion and meaning in life in the relationship between mindfulness and psychological well-being was both positive and significant (P<0.01). The results suggest that mindfulness facilitates positive re-evaluation and increases self-awareness, which contribute to the improvement of psychological well-being and the attainment of meaning in life for students who are experiencing the pressures of the entrance exam period.